Depression and Inflammatory Bowel Disease: A Bidirectional Two-sample Mendelian Randomization Study. (5th November 2021) - Luo, Jiao; Xu, Zhongwei; Noordam, Raymond; van Heemst, Diana; Li-Gao, Ruifang
Abstract: Background and Aims: Observational studies have suggested a bidirectional association between depression and inflammatory bowel disease [IBD], including Crohn's disease [CD] and ulcerative colitis [UC]. However, it remains unclear whether the observed associations are causal due to the difficulties of determining sequential temporality. We investigated the association between depression and IBD by using bidirectional two-sample Mendelian randomization [MR]. Methods: Independent genetic variants for depression and IBD were selected as instruments from published genome-wide association studies [GWAS] among individuals of predominantly European ancestry. Summary statistics for instrument–outcome associations were retrieved from three separate databases for both depression [Psychiatric Genomics Consortium, FinnGen and UK Biobank] and IBD [the largest GWAS meta-analysis, FinnGen and UK Biobank], respectively. MR analyses included the inverse-variance-weighted method, weighted-median estimator, MR-Egger regression, and sensitivity analyses of Steiger filtering and MR PRESSO. From either direction, analyses were performed per outcome database and were subsequently meta-analysed using a fixed-effect model. Results: Genetically predicted depression [per log-odds ratio increase] was associated with a higher risk of IBD; odds ratios [95% confidence interval] for IBD, CD and UC were 1.20 [1.05, 1.36], 1.29 [1.07, 1.56] and 1.22 [1.01, 1.47] in a combined sample size of 693 183 [36 507 IBD cases], 212 172 [13 714 CD cases] and 219 686 [15 691 UC cases] individuals, respectively. In contrast, no association was observed between genetically influenced IBD and depression in 534 635 individuals [71 466 depression cases]. Conclusions: Our findings corroborated a causal association of depression on IBD, which may impact the clinical decision on the management of depression in patients with IBD. Though our results did not support a causal effect of IBD on depression, further investigations are needed to clarify the effect of IBD activity on depression [with different symptomology].